Recent Advances in the Design of Targeted Iridium(III) Photosensitizers for Photodynamic Therapy - Huang, Huaiyi; Banerjee, Samya; Sadler, Peter J. (Chembiochem : a European journal of chemical biology, 2018)
Photodynamic therapy (PDT) is a noninvasive treatment for certain types of cancer, bacterial, fungal and viral infections, and skin diseases. In recent years, adaptation of this treatment so as to achieve more specific targeted cancer therapy in particular has attracted significant attention. We focus herein on the design of novel iridium‐based photosensitizers (PSs) with tunable photophysical and photobiological properties as efficient PDT agents. We highlight the ability of some IrIII photosensitizers to target specific cellular components, including their activation by one‐ and two‐photon irradiation. Provoke the Ir: Photodynamic therapy (PDT) can provide noninvasive cancer treatment. We summarize and highlight recent advances in the design of efficient iridium photosensitizers targeted to mitochondria, lysosomes, endoplasmic reticulum, nucleus, and even specific cellular proteins.